Against the churn: institutionalization, transformation, and restorative justice - Woolford, Andrew John (Contemporary justice review, 2025)
Drawing on twenty interviews conducted in 2022 with restorative justice practitioners and transformative justice advocates in Winnipeg, Manitoba, we examine how restorative justice navigates the churn of institutionalization. In Manitoba, this churn is strengthened through the creation of the Restorative Justice Centre as a government clearinghouse for referrals and funding. Simultaneously, anti-institutional philosophies of defunding, abolition, and decolonization have seen recent increased uptake among segments of the population. Based on our interviews, we argue that restorative programming in Manitoba has institutionalized to a degree that there is little optimism toward aligning or synthesizing restorative and transformative justice. But this does not mean each must remain its own solitude. Focusing on restorative justice and the threat of further institutionalization, we suggest restorative practitioners anchor themselves to transformative ideals, while also using transformative justice as a horizon by which they might seek to correct course when the pull of institutionalization becomes increasingly strong.